DINAMIKA KELOMPOK TANI MAESAAN WAYA DI DESA MANEMBO, KECAMATAN LANGOWAN SELATAN - Juwendi ., Poluan; Ventje V. Rantung; Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2017)
This research aims to identify the dynamics of Maesaan Waya Agriculture group which was studied by group dynamics elements namely the purpose of the group, the structure of the group, the building and the developing of the group, the unity of the group and the effectivity of the group. This research was conducted from October 2016 to April 2017 on Maesaan Waya Agriculture group in Manembo Village, South Langowan Subdistrict. The collecting of the data included primary and secondary data. Primary data was collected by direct interview using questionnaire with agriculture group members who were become respondents. The total number of respondents in this research is 20 respondents. The secondary data were collected from research-related literatures. Descriptive analysing was the method in data analyzing. The result of this research shows that the dynamics of Maesaan Waya agriculture group is categorized as dynamic with 80% valuation percentage. This is because the elements of group dynamics in Maesaan Waya agriculture group run well. Even though the elements of group dynamics run well, there was 20% dynamics elements categorized as less-dynamic.